A study on evaluating lipid profile of patients with diabetes mellitus - Abdul Majid, M.; Abdul Bashet, M.; Estiar Rahman, M.; Sabrina Moonajilin, M.; Ruhul Furkan Siddique, M. (International Journal Of Community Medicine And Public Health, 2019)
Background: The diabetic patients are at increased risk to develop lipid abnormalities (hyperlipidemia). Diabetic patients who have lipid abnormalities are more prone to develop cardiovascular diseases. The aim of the current study was to estimate lipid profiles of patients with type-2 diabetes mellitus at Savar area, Dhaka, Bangladesh. Methods: This was a multidisciplinary study conducted between January to April, 2017. A total of 105 known cases of type-2 diabetic patients were investigated. Demographic characteristics and clinical data situation of the patients were taken by interview questionnaire. About 5 ml of fasting venous blood sample was collected from each subject for biochemical analysis. Data obtained were analyzed using Statistical Package of Social Sciences (SPSS-IBM) version 22. Results: Out of 105 patients, 64.8% patients were male and 35.2% were female. The mean±SD for age of patients was 47.67±5.9. The pattern of lipid abnormalities estimated was high serum triglycerides (TGs) in 58.1% patients, high serum total cholesterol (TC) in 61.9%, low high-density lipoprotein cholesterol (HDL-C) in 44.8%, high low-density lipoprotein (LDL-C) in 53.3%. Among all the variables only HDL levels was found significantly associated with age group (p=0.043). Study also revealed that, among all the variables only LDL-C level was found significantly associated with education (p=0.028) and TC level was associated with gender (p=0.003). Conclusions: Hyperlipidemia is a common complication of diabetes mellitus. Therefore maintaining good lipid profile can prevent development and progression of related complications among patient with diabetes mellitus.